Factors Affecting People's Consumption Behavior Using Online Shops with Islamic Economic Perspective in Padangsidimpuan City - Darwis Harahap (Jurnal Ilmiah Ekonomi Islam, 2022)
Currently, e-commerce has become a shopping trend. People prefer to shop using online shops because there is a system of consumer freedom from having to go to stores that are far enough away and take a long time and consumers also have to leave the house to get the items they need. With ease and convenience, consumers prefer to transact in e-commerce to meet their various needs. However, now there has been a shift in shopping activities from fulfilling needs to desires that are redundant without being based on Islamic economic aspects. Therefore, this study aims to determine the relationship between the factors that influence online shop purchases through the accepted risk of people's consumptive behavior in the perspective of Islamic economics in Padangsidimpuan City. This research method uses Component Based Structure Equation Model (SEM) data analysis techniques and the model used is Loading Factor which is constructed from each factor studied using the Smart PLS 3 program tool. The price of online shop services with all the existing risks has a positive effect on people's consumptive behavior from an Islamic perspective.